2017
DOI: 10.1017/s0142716417000455
|View full text |Cite|
|
Sign up to set email alerts
|

Different phonological mechanisms facilitate vocabulary learning at early and late stages of language acquisition: Evidence from Polish 9-year-olds learning English

Abstract: To acquire a new word, learners need to create its representation in phonological short-term memory (STM) and then encode it in their long-term memory. Two strategies can enable word representation in STM: universal segmentation and phonological mapping. Universal segmentation is language universal and thus should predict word learning in any language, while phonological mapping is language specific. This study investigates the mechanisms of vocabulary learning through a comparison of vocabulary learning task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 71 publications
(146 reference statements)
2
15
0
Order By: Relevance
“…Children with poorer phonological awareness learned novel and non-novel words less accurately or more slowly ( Hu and Schuele, 2005 ; Hu, 2008 ). Longitudinally, phonological awareness plays a role when words are relearnt ( Hu, 2003 ) and phonological processing of novel words is based on sublexical representations, which are phonological and unstructured ( Marecka et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children with poorer phonological awareness learned novel and non-novel words less accurately or more slowly ( Hu and Schuele, 2005 ; Hu, 2008 ). Longitudinally, phonological awareness plays a role when words are relearnt ( Hu, 2003 ) and phonological processing of novel words is based on sublexical representations, which are phonological and unstructured ( Marecka et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This representation can later be encoded in long-term memory. The efficiency of this process depends on the range and quality of phonological representations already available to the learner (Marecka et al 2018). Studies confirmed that preexisting phonological knowledge supports vocabulary acquisition in L2 learners (Majerus et al 2008;Masoura and Gathercole 2005).…”
Section: Inspection Ofmentioning
confidence: 84%
“…We may attribute the significant gains in vocabulary to the integration of auditory-phonological and orthographic training. As outlined in the introduction, phonological awareness skills predict vocabulary acquisition in L1 and L2 learners (Kalia et al 2018;Marecka et al 2018), and phonological awareness training fosters word learning in children (de Jong et al 2000; Melby-Lervåg and Hulme 2010). Concerning L2 learners, phonological training boosts the acquisition of long-term phonological knowledge of the L2, e.g., sensitivity for the phoneme structure of words, and for phonemic features and phonotactic regularities that might be non-existent in L1.…”
Section: Inspection Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that better segmentation can lead to more efficient encoding of a novel word form (cf. Marecka et al, 2018 for an overview), high sensitivity to ART should make word learning much easier.…”
Section: Introductionmentioning
confidence: 99%